Las colocaciones de microcrédito de las instituciones financieras - Cáceres Zambrano, Jacinto Hipólito (2024)
The objective of this research work entitled “Microcredit placements by financial institutions” is to study the volumes of this segment placed in the local market by Private and Public Banks and Savings and Credit Cooperatives. Microcredits constitute a fundamental tool in the development of the Country, used by small entrepreneurs and microbusiness men who are poorly served by traditional Banking. Also know their participation in the development of work, income of their clients, as well as know the reasonableness of the interest rates and the levels of portfolio provision that the expert institutions in microcredit in Ecuador and the impact on their profitability. The information was collected through the websites of the Superintendency of Banks, Central Bank of Ecuador, Asobanca and Red Financiera de Desarrollo, which allowed us to evaluate the total amount of microcredit placements by financial institution to determine the amounts placed by this segment.......